Efektivitas Eco – Enzyme dalam Menurunkan TSS, TDS, Surfaktan pada Limbah Domestik dengan Variasi Proses Anaerob dan Koagulasi - Flokulasi - Firra Rosariawari; Ana Mauidatul Khasanah (Prosiding ESEC, 2022)
Rivers water resources have characteristics and properties different from other resources, where humans still need water to survive. The rapid growth of the population, especially in urban areas, has a serious impact on the decline in the carrying capacity of the environment. Eco-enzyme produced from simple fermentation of fresh vegetable or fruit waste, brown sugar, and water in a ratio of 1 : 3 : 10 is useful in reducing the level of pollution. Thus, the purpose of this study is to determine the effectiveness of eco-enzyme against the elimination of TSS, TDS, and Surfactant levels in domestic waste. In this study, we used variations in anaerobic processes and coagulation-flocculation with a concentration of eco-enzymes of 7,5% ; 5,0% ; 2,5%. Anaerobic processes take a residence time of 5, 10, 15 days. While the coagulation process – flocculation with 150 rpm on fast stirring for 1 minute, 60 rpm slow stirring for 15 minutes. Eco-fruit enzymes were more effective, the anaerobic process concentration of 5.0% was able to reduce the most optimal pollutant parameters by 8.70% for TSS, 62.42% for TDS, and 7.5% concentration by 98.87% at a stay of 15 days. While the coagulation – flocculation process with a concentration of 2.5% is able to set aside TSS by 7.33%, TDS by 42.07%, and concentration of 7,5% is able to set aside Surfactants by 96.29%.